The Impact of the Force Majeure on Contractual Obligatıons Special Report on the United Nations Convention on The Contracts for The International Sales of Goods (cisg) - Kapancı, Kadir Berk (International Academy of Comparative Law, 2022)
The effect of force majeure on contracts has possibly been the most debated subject of the law of contracts in the past two years. In this report, the effect of force majeure on the contracts for the international sale of goods will be analyzed withi n the context of the United Nations Convention on Contracts for the International Sale of Goods (CISG). Even though the CISG does not directly refer the concept offorce majeure, the issue is dealt with under the highly controversial article 79 of the CISG. In this report, the conditions and consequences of exemption from liability under the article 79 will be examined.
Keywords: Hardship; CISG; Force majeure; Strict liability; Sales contract; Exemption from liability